2019
DOI: 10.1177/2372732219862572
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Student Outcomes by Supporting Autonomy: Implications for Practice and Policy

Abstract: All students come to the classroom with inner motivational resources that, when supported, catalyze engagement, motivation, learning, and achievement. Teachers’ support for student autonomy is an essential tool for enhancing desirable student outcomes; practitioners and policy-makers can promote autonomy-supportive classroom environments. An overview of autonomy support presents core, autonomy-supportive practices: (a) providing choice opportunities, (b) providing rationales, and (c) incorporating student pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 60 publications
(82 reference statements)
3
27
0
2
Order By: Relevance
“…Based upon our results, as well as those demonstrated by Patall et al and Stefanou et al, it can be suggested that by providing students with the freedom of choice in an autonomy-supportive learning environment, students can follow their own interest and learning path [10,12]. This may lead to engagement and relatedness towards others in the course or even towards patients in pain.…”
Section: Course Setup and Basic Psychological Needssupporting
confidence: 82%
See 1 more Smart Citation
“…Based upon our results, as well as those demonstrated by Patall et al and Stefanou et al, it can be suggested that by providing students with the freedom of choice in an autonomy-supportive learning environment, students can follow their own interest and learning path [10,12]. This may lead to engagement and relatedness towards others in the course or even towards patients in pain.…”
Section: Course Setup and Basic Psychological Needssupporting
confidence: 82%
“…To stimulate students’ autonomy, teachers can use autonomy-supportive teaching strategies that are based on three main principles: offering choices in learning, providing a rationale for learning, and organizing learning in accordance with the learners’ perspective and interests [ 3 , 10 ]. As demonstrated by Garcia and Pintrich, giving choices, even as little as decision making, positively influenced students’ intrinsic goal orientation, task value, and self-efficacy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, TAS has also been found to predict greater need satisfaction, engagement, and well-being among many other positive outcomes (Patall & Zambrano, 2019). Fredricks et al (2010) found that teachers who included the freedom of choice alongside providing feedback and promoting active learning engendered a more stimulating learning environment and contributed to passion development over time.…”
Section: Autonomy Support and Passionmentioning
confidence: 99%
“…Moreover, students from autonomy-supportive classrooms experienced enhanced academic self-regulation, as well as overall psychological adjustment, enhanced learning, higher performance, and persistence (Patall et al, 2018). Given the many positive outcomes deriving from TAS, it is worthwhile pursuing research about the relationship between TAS and passion as most studies have thus far only suggested that teachers are either mostly indifferent or controlling in their classrooms (Patall & Zambrano, 2019). In addition, results from Mageau et al (2009) showed a similar pattern of findings in which individuals with parents who are autonomy supportive were more likely to experience HP versus OP.…”
Section: Autonomy Support and Passionmentioning
confidence: 99%
“…Þannig er sjálfraeði nemenda tengt áhugahvöt, sjálfstjórn og skuldbindingu nemenda til náms, námsskilningi, námsgengi, sjálfstrausti, sköpunargleði og vellíðan, svo eitthvað sé nefnt (sjá nánar í Reeve, 2009;Su og Reeve, 2011). Nýlegri rannsóknir hafa einnig staðfest þessar niðurstöður (til daemis Jang, Reeve og Halusic, 2016;Núnez og León, 2019;Patall og Zambrano, 2019;Yu, Li, Want og Zhang, 2016).…”
Section: Inngangurunclassified